Investigation of the effect of temperature cycling on surface features of sulfathiazole crystals during seeded batch cooling crystallization - Abu Bakar, Mohd Rushdi; Nagy, Zoltan K.; Rielly, Chris D. (American Chemical Society, 2010)
The effect of temperature cycling on the surface features of sulfathiazole crystals was investigated using focused beam reflectance measurement (FBRM) and ex situ optical microscopy, scanning electron microscopy (SEM), and atomic forced microscopy (AFM). Smoothing of the crystal surface was observed during heating, while during cooling the smooth crystals showed features growing on their surfaces. These changes on the crystal surface were detected by the FBRM as an increase in the number of coarse counts during heating phases and a drop during cooling phases. Laser beam spreading caused by the surface changes and signal/chord splitting due to the formation of sharp edges are suggested as explanations for the FBRM results. The study shows the capability of FBRM to provide useful information with regard to the changes on the surface of the crystalline products, which could be linked to possible growth mechanisms. The information can be used to avoid problems in the downstream processing or in the final product property due to variations in flowability and friability, which are related to the crystal surface property.